A Theoretical Formation of Emotional Intelligence in Terms of Childhood Trauma and Altered Self-Capacities among Adolescents - Tolegenova, A; Jakupov, S; 3Man Cheung Chung, M; Jakupov, M (Farabi Journal of Social Sciences, 2016)
The aim of this paper is twofold. Firstly, it aims to provide a brief review of literature pertaining to the relationship between psychological well-being and emotional intelligence among adolescents. Secondly, it aims to point out the gap in research looking at the link between EI and childhood trauma and to formulate a theoretical model for understanding the foregoing relationship. The theoretical postulate is integrated with theories from trauma and EI literature. In brief, it postulates that the experience of childhood trauma would have a significant impact on the development oftraumatized self among these adolescents. This traumatized self is characterized by altered self-capacities of which interpersonal conflicts or difficulties with oneself and others are part